How does environmental tax reform drive corporate innovation to green technologies? Quasi-natural experimental evidence from China - Hu, Hui; Zhu, Yuqi; Ye, Lin; Wang, Yulong (Journal of Business Economics and Management, 2025)
How to motivate enterprises to formulate green technology (GT) innovation is crucial for promoting green development and minimizing pollution control costs. This research employs a quasi-experimental approach to analyze the impact of environmental tax reform (ETR) on corporate innovation decisions. First, we construct a two-sector model within a single enterprise, where the enterprise produces goods using GT and non-green technology (NGT) respectively. ETR influences a company’s innovation choices by the relative market value, R&D intensity, and productivity of products manufactured using GT and NGT under profit maximization. Second, we test our model using 20122023 manufacturing firms’ data, and the empirical results confirm our theoretical predictions. Third, we perform robustness tests to exclude the impact of subsidies, command and control environmental supervision and the COVID-19 epidemic. Fourth, we conduct heterogeneity analysis in polluting level and market competition. Finally, this study uses two instrumental variables (IVs) to validate our main regression results: the interaction between regional water area and industrial chemical oxygen demand, and the proportion of days affected by temperature inversion. This study contributes to the literature related to innovation choices under environmental policy and has implications for directing firms’ innovation to GT.